INFLUENCE OF SOCIALIZATION, KNOWLEDGE, TRUST, AND SOCIO-ECONOMIC MODELS ON ZAKAT PAYMENT INTEREST BAITUL MAL - Anuriah, Shinta Laila; Riyaldi, Muhammad Haris (Universitas Syiah Kuala, 2024)
This study aims to examine the influence of Socialization, Knowledge, Trust and Socio-Economic Models on interest in paying zakat through Baitul Mal on Lambaro Main Market traders. The sample in this study was 110 traders taken using the Hair formula. The analysis method is multiple linear regression analysis. The results showed that partial Socialization had no effect on the interest in paying zakat to traders of the Lambaro Main Market. The Knowledge, Trust and Socio-Economic Model partially affect the interest in paying zakat to traders of the Lambaro Main Market. While simultaneously Socialization, Knowledge, Trust, and Socio-Economic Models affect the Interest in Paying Zakat to Lambaro Main Market Traders. Therefore, Baitul Mal can carry out outreach to traders in order to increase interest in paying zakat at Baitul Mal.